Inspired and Effective: The Role of the Ideal Self in Employee Engagement, Well-Being, and Positive Organizational Behaviors - Martinez, Hector A.; Rochford, Kylie; Boyatzis, Richard E.; Rodriguez-Chaves, Sofia (Frontiers in Psychology, 2021)
This study explores the efficacy of a specific tool – the articulation of the ideal self – in job engagement, psychological well-being, and organizational citizenship behavior. We hypothesized that employees who can visualize their jobs as part of their ideal self—in particular how it helps in its development and realization—would feel higher levels of engagement and fulfillment in their lives, as well as engage in greater amounts of helping and voice OCB. A total of 239 full time employees from five companies in Costa Rica filled out the ideal self questionnaire, the job engagement, and psychological well-being surveys, and were evaluated by their peers on task behavior and helping and voice OCB. Results of the SEM model showed that the ideal self was positively related to job engagement, psychological well-being and helping and voice. These findings contribute to the research on the impact and importance for organizations to help employees find meaningfulness in their work.